Effects of a Brief Motivational Interviewing Program on Self-Care motivation, Self-Care Behaviors, and Glomerular Filtration Rate among Patients with Chronic Kidney Disease - Arunsangsod, Kirana; Songwathana, Praneed (Journal of Thailand Nursing and Midwifery Council, 2023)
Introduction: Chronic kidney disease (CKD) is a global public health concern, with the number of patients increasing annually. Brief motivational interviewing is a critical strategy reported to be useful in encouraging patients with CKD to better understand how to self-care and reduce risky behaviors, thereby slowing down and preventing kidney degeneration. Objective: To investigate the effects of a brief motivational interviewing program on self-care motivation, self-care behaviors, and glomerular filtration rate (GFR) among patients with CKD. Design: A quasi-experimental design with two-group pretest–posttest Methodology: The participants were 60 patients with CKD stage 3-4 who attended the CKD clinic at a secondary care hospital in Narathiwat province. They were purposively selected based on inclusion criteria and assigned to either an experimental group (n=30) that received usual care and a brief motivational interviewing program consisting of eight sessions and a follow-up period of 20 weeks or a control group (n=30) that received only usual care. Data on self-care motivation (with test-retest reliability of .97), self-care behaviors (with Cronbach’s Alpha coefficient .75), and GFR were collected using questionnaires at baseline and after 20 weeks. Data were analyzed using descriptive statistics, the Chi-Square test, Wilcoxon Signed Ranks test, and Mann-Whitney U test. Results: The participants were mainly male elderly with low levels of self-motivation and self-care behaviors. After 20 weeks of the program, the experimental group had significantly increased average scores on self-care motivation, self-care behaviors, and GFR (Z = -4.487, p <.001; Z = -4.547, p <.001; Z = -2.725, p=.006, respectively). The control group had average scores on self-care behaviors and GFR decreased lower than those of the baseline assessment. The mean different scores of the self–care motivation, self-care behaviors, and GFR of the experimental group were statistically and significantly higher than those of the control group (Z=-2.221, p=.026; z=-3.432, p<.001; Z=-4.531, p<.001, respectively). This study indicates that a brief motivational interviewing program has significant positive effects on self-care motivation, self-care behaviors, and GFR among patients with CKD stage 3-4. Recommendations: Nurses and healthcare teams can apply the brief motivational interviewing program to promote better self-motivation and self-care behaviors in patients with stage 3-4 chronic kidney diseases. Additionally, continuous monitoring can be implemented to potentially delay disease progression.